2018
DOI: 10.1155/2018/5403795
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation, and Hygiene Service Availability at Rural Health Care Facilities in Southwestern Uganda

Abstract: There is a paucity of information on the state of water, sanitation, and hygiene (WASH) at health care facilities in Uganda. A survey on WASH service availability was conducted at 50 health care facilities across 4 districts of rural southwestern Uganda between September and November 2015. The main water points at the majority (94%) of the health care facilities were improved sources, while improved toilets were available at 96% of the health care facilities visited. Hospitals had the poorest toilet to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 9 publications
3
25
2
Order By: Relevance
“…There is limited data on WASH in HCFs in urban Uganda, however, a study conducted in south western Uganda indicated critical gaps in the provision of WASH in HCFs in rural facilities (4). In this study, only 38% of the HCFs had toilets with hand washing facilities; with only 24% having soap and water (4).…”
Section: Introductionmentioning
confidence: 57%
“…There is limited data on WASH in HCFs in urban Uganda, however, a study conducted in south western Uganda indicated critical gaps in the provision of WASH in HCFs in rural facilities (4). In this study, only 38% of the HCFs had toilets with hand washing facilities; with only 24% having soap and water (4).…”
Section: Introductionmentioning
confidence: 57%
“…More PNFP HCFs had better WASH services compared to the public HCFs. It has been assumed that private facilities at the same level as public facilities generally have better service standards (4). Unlike public HCFs where services are free, PNFP HCFs in the study area provide healthcare services at a cost.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data on WASH in HCFs in urban Uganda, however, a study conducted in south western Uganda indicated critical gaps in the provision of WASH in HCFs in rural facilities (4). Mulogo,Matte (4) reported that only 38% of the HCFs had toilets with hand washing facilities; with only 24% having soap and water (4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations